Mineral filled porous composites based on polyvinylpyrrolidone copolymers with bactericidal properties - Skorokhoda, Volodymyr; Semenyuk, Nataliya; Dziaman, Iryna; Suberlyak, Oleg (Publishing House of Lviv Polytechnic National University, 2016)
The polymerization of 2-hydroxyethylmethacrylate compositions with polyvinylpyrrolidone has been investigated in the presence of mineral fillers (hydroxyapatite, montmorillonite and wollastonite). The influence of the nature and amount of mineral filler on polymerization kinetics and composition of copolymers has been determined. In the composite structure silver particles were obtained via silver nitrate reduction by polyvinylpyrrolidone tertiary nitrogen. The synthesized silver-containing composites possess bactericidal properties against E. colі and S. aureus bacteria, in particular. Досліджено полімеризацію композицій 2-гідроксіетилметакрилату з полівінілпіролідоном у присутності мінеральних наповнювачів (гідроксіапатиту, монтморилоніту і воластоніту). Встановлено вплив природи та кількості мінерального наповнювача на кінетику полімеризації і склад кополімерів. Підтверджено можливість одержання в структурі композиту частинок срібла реакцією відновлення нітратів срібла третинним атомом нітрогену полівінілпіролідону. Синтезовані срібловмісні композити проявляють фунгібактерицидні властивості, зокрема, проти Escherichia coli, Staphylococcus aureus і Aspergillus niger.
Пористі композити на основі мінерально наповнених кополімерів полівінілпіролідону з бактерицидними властивостями
Keywords: 2-hydroxyethylmethacrylate; polyvinylpyrrolidone; silver nanoparticles; hydroxyapatite; montmorillonite; wollastonite; 2-гідроксіетилметакрилат; полівінілпіролідон; наночастинки срібла; гідроксіапатит; монтморилоніт; воластоніт